GRAPHIC ORGANIZER TO IMPROVE STUDENTS’ NARRATIVE TEXT WRITING - Messyana, Lourensia; Sutapa Y, Y. Gatot; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was aimed to solve students’ writing problem in narrative text by using graphic organizer on class XI IPS 1 of SMA Santo Fransiskus Asisi Pontianak in academic year 2016/2017. It was focused on determining the generic structure. The research design of this study was classroom action research. The 39 students of class XI IPS 1 were participating in this research. The researcher observed the students’ improvement in writing by collecting data through observation checklist, field notes and achievement test.  It was obtained from observation checklist that most of the students showed better attention in learning narrative writing using graphic organizer while the teacher was encouraging them to write. Based on field notes, it was discovered that the students can write the narrative text by having brainstorming and being guided on graphic organizer itself. After administered achievement test, the teacher found almost of the students can write the whole story by noticing the text organization and vocabulary choice. In the cycle, the researcher found that, the students could use graphic organizer to organize sequence of actions by using simplified questions which are related to the plot. From all of the result, it can be inferred that graphic organizer improves students’ narrative text writing. Key words: narrative writing, graphic organizer, classroom action research